An Implementation of Hybrid Genetic Algorithm for Clustering based Data for Web Recommendation System - Shrivastava, Animesh; Rajawat, Singh (International Journal of Computer Sciences and Engineering, 2014)
Web Mining is an interesting domain in information processing that includes a large variety of applications i.e. recommendation system design, next user web page prediction, navigational pattern analysis and others. In this paper a new hybrid clustering algorithm is proposed and implemented using Genetic algorithm and K-NN algorithm and the implementation of desired algorithm is given using a web recommendation system which analyze user navigational pattern from web server access log file and recommends the next user web page. The performance of the designed system is evaluated and listed in this paper. According to the results, the proposed hybrid approach is efficient and effective for the given application domain.